Avaliação da adição de gesso e do revolvimento em pilhas de compostagem e na qualidade do composto de esterco de ave poedeira - Santos, Fabiano Goellner dos (2008)
Laying poultry manure is the main waste generated in the egg production industry which requires an infra-structure to treat this kind of residue. Commonly, this waste has been used as a fertilizer, but no previous treatment and sanitary control has been employed before soil application. Composting is an alternative to treat this kind of waste, stabilizing the organic matter, but decreases the level of nitrogen (N) content of the manure. The utilization of gypsum and simple superphosphate (SSP) as additives in laying poultry manure has been proposed to reduce N losses as ammonia, although there is no agreement about the efficiency and quantities that these materials should be used. The objective of this study was to evaluate the effectiveness of these additives and the turner effect on laying poultry manure compost quality, mainly on N content. Two experiments were performed: Experiment 1, using openwindrow composting, and Experiment 2, using micro-heaps in plastic greenhouse. On Experiment 1, 6 % of gypsum, from construction and demolition waste, was tested, as well as the effect of turning the heaps. In this experiment, beyond the levels of N total, the levels of mineral N, carbon (C), C:N rate, pH in water and in CaCl2, electrical conductivity (EC), moisture content, temperature, occurrence of helminthes and pathogenic microorganisms, and toxic metals analysis were assessed in the compounds. The total and mineral N contents, in the piles of Experiment 1 varied with the time of composting and they decreased significantly in the first three weeks. Although the compound with higher content of total N was obtained when the poultry manure has been composted in piles with gypsum, the monitoring of the piles of composting showed that over the 95 days, the content of this form of N did not vary between piles with or without gypsum. The turning did not change the N level of the composts. There was no difference on the occurrence of pathogenic microorganism indicators among the treatments. The population of these microorganisms in the compound attended the Brazilian Federal standards of quality. The opposite was found for eggs of helminths in piles not turned and without gypsum. In the Experiment 2, up to 19.5 kg S t-1 was added to the manure, as either gypsum or SSP. The micro-heaps were not turned in this experiment and the total N, pH as CaCl2, and sulphur contents were evaluated. The efficiency of gypsum to decrease the N losses in the micro-heaps was low, while the SSP was more efficient. Among the S sources and rates tested, the highest content of total N in the composts were observed with the addition of 15.6 kg S t-1 as SSP (4.5 % of N), reducing about 50 % the N loss in comparison with the control (micro-heaps without S). The highest level of total N (2.8 %) in the micro-heaps with gypsum was found at the higher rate tested, avoiding the loss of about 25 % of the N content